Model of three-way decision based on the space of set pair information granule and its application - Chun-ying ZHANG; Li-ya WANG; Ming-xia LI; Bao-xiang LIU (Tongxin xuebao)
Through the analysis of the existing theory and method of three-way decision,model of three-way decision based on the space of set pair information granule was proposed,which was to explain the intension and extension of three-way decision on the view of unity of opposites.Firstly the space structure of set pair information granule can be di-vided into positive granule,negative granule,different granule,which were similar and slightly different with three re-gions of generalized three-way decision.The three kinds of information granules in set pair information granule space were built based on certain positive degree,negative degree and different degree.Secondly,according to the given threshold,set pair information granule is divided into mutually disjointing positive region,negative region and different region.Based on these three regions,the computing method of decision loss function is put forward,and the process of decision-making algorithm is obtained use the three-way decision method of set pair information granule space to evalu-ate and make decision on risk investment,then good decision results have been achieved.